2009
DOI: 10.1016/j.cmet.2009.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Enhance Insulin Sensitivity

Abstract: SUMMARY Chronic reactive oxygen species (ROS) production by mitochondria may contribute to the development of insulin resistance, a primary feature of type 2 diabetes. In recent years it has become apparent that ROS generation in response to physiological stimuli such as insulin may also facilitate signaling by reversibly oxidizing and inhibiting protein tyrosine phosphatases (PTPs). Here we report that mice lacking one of the key enzymes involved in the elimination of physiological ROS, glutathione peroxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
437
4
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 523 publications
(480 citation statements)
references
References 48 publications
16
437
4
6
Order By: Relevance
“…Grey and black bars represent control and Pgc-1β -overexpressing muscles, respectively relationship exists between ROS production and insulin action. Intermittent, low-level ROS production has been reported to enhance insulin action via improvements in insulin signal transduction [50]. However, other recent studies have shown that excessive or persistent generation of ROS in mitochondria contributes to the pathogenesis of insulin resistance [10,11].…”
Section: Discussionmentioning
confidence: 96%
“…Grey and black bars represent control and Pgc-1β -overexpressing muscles, respectively relationship exists between ROS production and insulin action. Intermittent, low-level ROS production has been reported to enhance insulin action via improvements in insulin signal transduction [50]. However, other recent studies have shown that excessive or persistent generation of ROS in mitochondria contributes to the pathogenesis of insulin resistance [10,11].…”
Section: Discussionmentioning
confidence: 96%
“…Thus it has been shown that insulin stimulates the generation of ROS, since when insulin binds to its receptor, a short burst of cellular ROS is produced, acting as second messenger that mediates insulin signalling [34,35]. Furthermore, Loh et al [36] demonstrated that subtle increases in ROS production were in fact associated with improved insulin sensitivity in mice deficient in the cytosolic antioxidant GPx1, suggesting that ROS may even help enhance insulin sensitivity. At the same time, overabundance of GPx1 resulted in hyperglycaemia, hyperinsulinaemia and insulin resistance in mice [37], indicating that H 2 O 2 quenching disrupts insulin action.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, studies have also shown that a transient physiological increase in ROS may be essential for a training-induced increase in insulin sensitivity in type 2 diabetes patients [20] and for protection against high-fat diet-induced insulin resistance in rodents [21]. Both these studies [20,21] suggest that ROS have a beneficial effect when increased ROS is transient, but are harmful when the increased concentration is sustained, as seen in response to chronic hyperglycaemia and dyslipidaemia.…”
Section: Introductionmentioning
confidence: 99%